Pembinaan Sikap Disiplin Mahasiswi melalui Pengurus Badan Eksekutif Mahasiswi Ma’had - Uswatun Hasanah; Khairotul Imamah; Moh. Wardi (Fakultas Agama Islam Universitas Billfath, 2022)
This study investigated the role of the BEMA administrator in developing student discipline with the aim of describing the role of the BEMA administrator (Ma’had Executive Body) in developing student discipline and controlling the BEMA administrator (Ma’had Executive Body) in developing student discipline. This study uses a qualitative method with a type of case study. There are two sources of data used in this study, primary and secondary data sources. Primary data sources are obtained from interviews with BEMA managers and semester II and IV students and supported by observation. While secondary data sources are other data that can support research that has received data absent intensive student worship IDIA Printing, infringement journals and TENGKO. It can be concluded from the research carried out that, the role of the BEMA manager in shaping the student discipline attitude is three, namely as an example or as a usurper of passion, as an organizer and as a disciplinary advocate. While managers' control of student discipline has two, the first, internal factors, namely lack of skill or organizational skills, the two external factors, differences in character and selfishness.